Prevalence of reported cases of dirofilariasis between 2021 and 2024 and the main diagnostic methods used (Research, Society and Development, 2025)
The dirofilariasis is a parasitic disease caused by the filarial nematode Dirofilaria immitis, transmitted through mosquitoes, and is of great importance in Veterinary Medicine, mainly due to its cardiopulmonary impacts on dogs and cats. The present study had as a goal to analyze the prevalence of reported cases of dirofilariasis in Brazil between 2021 and 2024, as well as to identify the main diagnostic methods used. A total of 15 case reports written in Portuguese and freely available online in full, were analyzed, revealing a progressive increase in the number of reported cases over the years. The coastal regions showed the highest prevalence, which can be attributed to favorable climatic conditions for vector proliferation, such as high humidity and temperature. Among the diagnostic methods, the immunochromatographic SNAP test stood out in veterinary clinical practice due to its speed, practicality, and accessibility. It is concluded that dirofilariasis has become increasingly relevant in the national context, emphasizing the importance of early diagnosis and epidemiological surveillance for effective disease control.